The emerging and diverse roles of the SLy/SASH1‐protein family in health and disease—Overview of three multifunctional proteins. Issue 4 (12th March 2021) - Jaufmann, Jennifer; Franke, Fabian Christoph; Sperlich, Andreas; Blumendeller, Carolin; Kloos, Isabel; Schneider, Barbara; Sasaki, Daisuke; Janssen, Klaus‐Peter; Beer‐Hammer, Sandra
Abstract: Intracellular adaptor proteins are indispensable for the transduction of receptor‐derived signals, as they recruit and connect essential downstream effectors. The SLy/SASH1‐adaptor family comprises three highly homologous proteins, all of them sharing conserved structural motifs. The initial characterization of the first member SLy1/SASH3 (SH3 protein expressed in lymphocytes 1) in 2001 was rapidly followed by identification of SLy2/HACS1 (hematopoietic adaptor containing SH3 and SAM domains 1) and SASH1/SLy3 (SAM and SH3 domain containing 1). Based on their pronounced sequence similarity, they were subsequently classified as one family of intracellular scaffold proteins. Despite their obvious homology, the three SLy/SASH1‐members fundamentally differ with regard to their expression and function in intracellular signaling. On the contrary, growing evidence clearly demonstrates an important role of all three proteins in human health and disease. In this review, we systematically summarize what is known about the SLy/SASH1‐adaptors in the field of molecular cell biology and immunology. To this end, we recapitulate current research about SLy1/SASH3, SLy2/HACS1, and SASH1/SLy3, with an emphasis on their similarities and differences.